Intraoperative bronchoscopic visualization of left ventricular assist device thrombus. (July 2016) - Yost, Gardner; Bhat, Geetha; Modi, Sejal; Pappas, Pat; Tatooles, Antone
Despite advancements in left ventricular assist device (LVAD) design and clinical management, device thrombosis remains a pertinent complication. Limited imaging makes precise visualization of clot location and shape very challenging. We report the usage of videobronchoscopic exploration of explanted LVADs for direct visualization of clot in two patients. This technique is a rapid and inexpensive means of improving our understanding of LVAD clot formation and may be useful in surgical exploration of inflow and outflow tracts during LVAD exchange.